2022
DOI: 10.1111/jopr.13554
|View full text |Cite
|
Sign up to set email alerts
|

Physical, Mechanical, and Anti‐Biofilm Formation Properties of CAD‐CAM Milled or 3D Printed Denture Base Resins: In Vitro Analysis

Abstract: To investigate surface characteristics (roughness and contact angle), anti-biofilm formation, and mechanical properties (mini-flexural strength) of computeraided design and computer-aided manufacturing (CAD-CAM) polymethylmethacrylate (PMMA) polymer, and three-dimensional (3D) printed resin for denture base fabrication compared with conventional heat polymerized denture base resins. Materials and methods: A total of 60 discs and 40 rectangular specimens were fabricated from one CAD-CAM (AvaDent), one 3D printe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 33 publications
3
47
0
Order By: Relevance
“…Hydrophobic materials have been reported to be more prone to C. albicans adhesion through hydrophobic interactions between the denture surface and the hydrophobic cell surface [ 48 ]. Two previous studies [ 49 , 50 ] compared the hydrophobicity of 3D-printed resin with that of conventional PMMA. Freitas et al [ 49 ] found that 3D-printed resin showed a lower contact angle (indicating greater hydrophilicity) when compared with conventional PMMA acrylic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrophobic materials have been reported to be more prone to C. albicans adhesion through hydrophobic interactions between the denture surface and the hydrophobic cell surface [ 48 ]. Two previous studies [ 49 , 50 ] compared the hydrophobicity of 3D-printed resin with that of conventional PMMA. Freitas et al [ 49 ] found that 3D-printed resin showed a lower contact angle (indicating greater hydrophilicity) when compared with conventional PMMA acrylic.…”
Section: Discussionmentioning
confidence: 99%
“…Two previous studies [ 49 , 50 ] compared the hydrophobicity of 3D-printed resin with that of conventional PMMA. Freitas et al [ 49 ] found that 3D-printed resin showed a lower contact angle (indicating greater hydrophilicity) when compared with conventional PMMA acrylic. However, 3D-printed resins showed the highest C. albicans adhesion among the tested resins, which was mainly attributed to their surface roughness.…”
Section: Discussionmentioning
confidence: 99%
“…31 32 The degree of polymerization may be influenced by the efficacy of the postrinsing procedure, which ensures the elimination of uncured resin and reduces the existence of unreacted monomers. 33 The findings indicated that automated procedures rinsing for 15 minutes produced the greatest DC score; however, no statistically significant differences were seen among the other methods. When postrinsing time is taken into account, a longer postrinsing time may facilitate the removal of residues from the uncured resin layer, therefore increasing the surface object's exposure to UV radiation and enabling polymerization to occur during the postpolymerizing stage.…”
Section: Discussionmentioning
confidence: 86%
“…Mokhtar et al observed that bacterial adhesion on MA materials was influenced by fabrication methods (AM, SM, and heat/cold curing), with AM showing the best results [ 15 ]. Results were heterogenous, since more C. albicans was observed on AM specimens compared to SM ones [ 43 ]. Although a significant effect of the building angle on surface roughness/topography was previously reported, no relevant difference in the adhesion of Candida albicans was observed [ 24 ].…”
Section: Discussionmentioning
confidence: 99%